2016
DOI: 10.3748/wjg.v22.i15.3969
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase overexpression promotes epithelial-mesenchymal transitionvianuclear factor-κB signaling in colorectal cancer cells

Abstract: ILK overexpression improved the proliferation, metastasis, and invasion ability of SW480 cells, and this effect may be mediated by the NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…The current study verified that emodin weakened the migration and invasion abilities of A2780 and SK-OV-3 by inhibiting EMT via targeting ILK. This result is consistent with a previous study which confirmed that ILK overexpression promotes epithelial-mesenchymal transition in colorectal cancer cells [35]. …”
Section: Discussionsupporting
confidence: 94%
“…The current study verified that emodin weakened the migration and invasion abilities of A2780 and SK-OV-3 by inhibiting EMT via targeting ILK. This result is consistent with a previous study which confirmed that ILK overexpression promotes epithelial-mesenchymal transition in colorectal cancer cells [35]. …”
Section: Discussionsupporting
confidence: 94%
“… 20 , 29 ILK has been reported to facilitate cancer cell migration and invasion by regulating EMT processes. 15 , 30 , 31 Consistently, the knockdown of ILK inhibited tumor invasion and metastasis by inhibiting the EMT process in bladder cancer and in oral squamous cell carcinoma. 17 , 32 In the present study, we found that the overexpression of ILK of A2780 and SK-OV-3 cells had a greater potential for proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 68%
“…Among them, ILK was selected as key candidate based on the central signal transducing location in protein-protein interaction network and its key role in cancer progression and cancer cell motility. It has been proven that overexpression of ILK was crucial for carcinogenesis and metastasis in assorted cancer types, including colorectal cancer [8], renal cell carcinoma [11], thyroid cancer [12], breast cancer [6,13], non-small cell lung cancer [17,18], prostate cancer [19,20]. In colorectal cancer cells, overexpression of ILK promoted proliferation, metastasis, and invasion ability.…”
Section: Discussionmentioning
confidence: 99%
“…It has dual effects in the process of carcinogenesis, progression and metastasis. Firstly, ILK regulates multiple signal transduction pathways, including AKT, GSK-3β, Nf-κB, Erk and β-catenin signaling pathway [5][6][7][8][9]. Secondly, ILK forms a scaffold complex with some cytoskeleton proteins and plays a crucial role in regulating cell motility, cytoskeleton reorganization, focal adhesion, tumor progression and invasion [10].…”
Section: Ivyspringmentioning
confidence: 99%